Integrative in silico and in vivo Drosophila model studies reveal the anti-inflammatory, antioxidant, and anticancer properties of red radish microgreen extract - Trina Ekawati Tallei; Nova Hellen Kapantow; Nurdjannah Jane Niode; Sofia Safitri Hessel; Maghfirah Savitri; Fatimawali Fatimawali; Sojin Kang; Moon Nyeo Park; Muhammad Raihan; Widya Hardiyanti; Firzan Nainu; Bonglee Kim (Scientific Reports)
Abstract Red radish microgreens (RRM) have gained considerable attention for their promising therapeutic potential. However, the molecular mechanisms underlying their bioactivity remain inadequately characterized. This study explores the anti-inflammatory, antioxidant, and anticancer properties of RRM extract using in silico and in vivo Drosophila model analyses. The metabolite profile of the RRM extract was characterized using comprehensive metabolomics techniques, including Gas Chromatography-Mass Spectrometry (GC-MS) and Liquid Chromatography High-Resolution Mass Spectrometry (LC-HRMS). Furthermore, in silico analysis utilizing network pharmacology identified target proteins of RRM compounds associated with cancer, inflammation, and oxidative stress. Concurrently, in vivo experiments with Drosophila melanogaster PGRP-LB Δ (Dm PGRP-LB Δ ) larvae was conducted to assess the extract’s impact on immune and oxidative stress pathways. In silico analysis revealed that RRM compounds interacted with key proteins (AKT1, ESR1, MAPK1, SRC, TP53), modulating pathways related to cancer, inflammation, and oxidative stress. Molecular dynamics simulations reinforced the docking results by confirming robust binding of kaempferitrin to AKT1. In vivo studies showed that RRM extract suppressed immune-related genes (dptA, totA) through the NFκB and JAK-STAT pathways, reduced ROS levels, and selectively regulated antioxidant gene expression by enhancing sod1 while decreasing sod2 and cat. These results suggest RRM extract as a functional food for managing oxidative stress, inflammation, and cancer. Further research in higher organisms and clinical settings is needed.